Design and evaluation: End users, user datasets and personas. (January 2015) - Marshall, Russell; Cook, Sharon; Mitchell, Val; Summerskill, Steve; Haines, Victoria; Maguire, Martin; Sims, Ruth; Gyi, Diane; Case, Keith
Abstract: Understanding the needs and aspirations of a suitable range of users during the product design process is an extremely difficult task. Methods such as ethnographic studies can be used to gain a better understanding of users needs, but they are inherently time consuming and expensive. The time pressures that are evident in the work performed by design consultancies often make these techniques impractical. This paper contains a discussion about the use of 'personas', a method used by designers to overcome these issues. Personas are descriptive models of archetypal users derived from user research. The discussion focuses on two case studies, the first of which examines the use of personas in the car design process. The second examines the use of personas in the field of 'inclusive design', as demonstrated by the HADRIAN system. These case studies exemplify the benefits 'data rich' personas contribute as opposed to 'assumption based' personas.